The Role of Cerebral Embolic Protection Devices During Transcatheter Aortic Valve Replacement - Demir, Ozan M.; Iannopollo, Gianmarco; Mangieri, Antonio; Ancona, Marco B.; Regazzoli, Damiano; Mitomo, Satoru; Colombo, Antonio; Weisz, Giora; Latib, Azeem (Frontiers in Cardiovascular Medicine, 2018)
Transcatheter aortic valve replacement is the therapy of choice for patients with severe aortic stenosis who have prohibitive or high surgical risk. However, the benefit of TAVR is attenuated by the occurrence of major disabling stroke which is associated with increased mortality and early-reduced quality of life. Despite advances in TAVR technology, stroke remains a serious complication that is associated with significant negative outcomes. The majority of these occur in the acute phase following TAVR where cerebral embolic events are frequent. Cerebral embolic protection devices (CEPD) have been developed to minimize the risk of peri-procedural ischemic stroke during TAVR. CEPD have the potential to reduce intraprocedural burden of new silent ischemic injury. In this review we outline the etiology and incidence of stroke in TAVR population, and systematically review current evidence for cerebral embolic protection devices.